Application of Controlling Instruments for Strategic Planning in Small and Medium-Sized Enterprises - Zeljko SUDARIC; Valentina VINSALEK STIPIC (Communications of International Proceedings, 2023)
This paper attempts to find an answer to the question of what are the possibilities and limitations of using controlling instruments in the function of strategic planning in small and medium-sized enterprises. It is pointed out that such instruments, which are most often used in large companies, should find their application in small and medium-sized companies, as indispensable advisory help to managers. The paper additionally explains the specifics of strategic planning in small and medium-sized enterprises, and investigates the relevant factors that influence the success of strategic planning in these smaller economic systems, where the application of strategic instruments is insufficient, and controlling is only one of many limiting circumstances. The specificity of this paper is that it investigates the hitherto rarely analyzed role of the Balanced Scorecard (BSC) as a strategic planning instrument in small and medium-sized enterprises. The aim of this paper is to investigate the application of BSC in strategic business planning of small and medium-sized enterprises in the Republic of Croatia. Accordingly, the following research hypotheses were set: H 1 – Controlling instruments for strategic planning are rarely applied in small and medium-sized enterprises; and H 2 – There are numerous limiting factors for the application of controlling instruments and definition of business strategy in small and medium-sized enterprises. As a result of the research, on a sample of 136 small and medium-sized companies operating in the Republic of Croatia, both research hypotheses were confirmed.
Keywords: strategic management; strategic controlling instruments; small and medium enterprises; strategic planning in small and medium enterprises